Biosorption of Microelements by Spirulina: Towards Technology of Mineral Feed Supplements - Agnieszka Dmytryk; Agnieszka Saeid; Katarzyna Chojnacka (The Scientific World Journal)
Surface characterization and metal ion adsorption properties of Spirulina sp. and Spirulina maxima were verified by various instrumental techniques. FTIR spectroscopy and potentiometric titration were used for qualitative and quantitative determination of metal ion-binding groups. Comparative FTIR spectra of natural and Cu(II)-treated biomass proved involvement of both phosphoryl and sulfone groups in metal ions sorption. The potentiometric titration data analysis provided the best fit with the model assuming the presence of three types of surface functional groups and the carboxyl group as the major binding site. The mechanism of metal ions biosorption was investigated by comparing the results from multielemental analyses by ICP-OES and SEM-EDX. Biosorption of Cu(II), Mn(II), Zn(II), and Co(II) ions by lyophilized Spirulina sp. was performed to determine the metal affinity relationships for single- and multicomponent systems. Obtained results showed the replacement of naturally bound ions: Na(I), K(I), or Ca(II) with sorbed metal ions in a descending order of Mn(II) > Cu(II) > Zn(II) > Co(II) for single- and Cu(II) > Mn(II) > Co(II) > Zn(II) for multicomponent systems, respectively. Surface elemental composition of natural and metal-loaded material was determined both by ICP-OES and SEM-EDX analysis, showing relatively high value of correlation coefficient between the concentration of Na(I) ions in algal biomass.